Workshop Pembuatan Rapor Secara Otomatis dengan Google Workspace di SMK IDN Boarding School Jonggol - Dedi Gunawan; Muhammad Mufti Ramdhani; Edi; Doni Azizi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Advances in technology make it easy for everyone with regards to the ease of obtaining and managing information. One clear example is the development of the internet which has become an icon of technological development. Especially in the era of education 4.0, the internet plays an important role in the educational process. In the era of education 4.0 educators and students are required to be able to integrate technology in every educational activity. One of the applications of technology in education today is the existence of an internet-based report card information system or what we usually know as online report cards. This service is a literature study that aims to collect information related to the use of the online report card information system implemented by several schools. The results obtained from this literature study are that the online report card system makes it easy for educators or teachers at SMK IDN Boarding School Jonggol to process student value data which can be accessed by both students and parents